2023
DOI: 10.1093/heapol/czad021
|View full text |Cite
|
Sign up to set email alerts
|

Political economy analysis of subnational health management in Kenya, Malawi and Uganda

Abstract: The need to bolster primary health care (PHC) to achieve the Sustainable Development Goal (SDG) targets for health is well recognized. In Eastern and Southern Africa, where governments have progressively decentralized health decision-making, health management is critical to PHC performance. While investments in health management capacity are important, so is improving the environment in which managers operate. Governance arrangements, management systems and power dynamics of actors can have a significant influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In this assessment, budget allocation was mentioned as a barrier more often by DHMT staff than providers (54% vs. 41%). At the subnational level, underfunded budgets and misalignment between policy, planning and budgeting sometimes occurs [30,31]. Results from an analysis of the political economy of subnational health sector planning and budgeting in three counties in Kenya revealed that while devolution has resulted in expanded participation in subnational health management, budget allocation has become more politicized so may not be directly aligned with national priorities [32].…”
Section: Discussionmentioning
confidence: 99%
“…In this assessment, budget allocation was mentioned as a barrier more often by DHMT staff than providers (54% vs. 41%). At the subnational level, underfunded budgets and misalignment between policy, planning and budgeting sometimes occurs [30,31]. Results from an analysis of the political economy of subnational health sector planning and budgeting in three counties in Kenya revealed that while devolution has resulted in expanded participation in subnational health management, budget allocation has become more politicized so may not be directly aligned with national priorities [32].…”
Section: Discussionmentioning
confidence: 99%
“…We used a problem-driven Political Economic Analysis (PEA) adapted from Overseas Development Institute (ODI) framework(14, 15, 43) to guide our analysis. This framework offers flexibility in analyzing specific policies across a wide spectrum of issues(44, 45).…”
Section: Methodsmentioning
confidence: 99%
“…We employed framework analysis(48, 49) using the transcribed verbatim from all the audio records of the FGD. We constructed a matrix to display the participants’ arguments against the PEA framework, from which we derived keywords to align with the themes and sub-themes outlined in the PEA for each commodity category (see Appendix S3), adopted from Rodríguez et al, 2023 (14). A cross-member checking was performed to ensure rigorous data analysis process.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations